The Effectiveness of CBT Group Counseling in Improving Self-Esteem of Victims of Verbal Bullying: A Pre-Experimental Study in Senior High Schools in Banjarmasin - Dwita Oktavia; Jarkawi; Sri Ayatina Hayati (Universitas PGRI Yogyakarta, 2026)
Verbal bullying remains a pervasive issue in Indonesian educational settings, significantly undermining adolescent self-esteem and mental health. This study examines the effectiveness of Cognitive Behavioral Therapy (CBT) group counseling in improving self-esteem among victims of verbal bullying in senior high schools in Banjarmasin. Employing a pre-experimental one-group pretest-posttest design, the research involved 139 Grade X students, with 8 identified as verbal bullying victims through purposive sampling. The intervention comprised three CBT counseling sessions incorporating cognitive restructuring and assertiveness training. Data were collected using a validated self-esteem questionnaire (Cronbach's α = 0.726) and analyzed through paired t-tests following normality and homogeneity checks. Results revealed a statistically significant increase in self-esteem scores from pretest to posttest (p = 0.003), with participants demonstrating improved self-perception, reduced social avoidance, and enhanced classroom participation. While findings support CBT's potential effectiveness in addressing bullying-related low self-esteem, the pre-experimental design and small sample size limit causal inferences. This study contributes evidence for integrating CBT-based group counseling into school anti-bullying programs in the Indonesian context, though randomised controlled trials are recommended to establish definitive efficacy. The intervention offers practical strategies for school counselors to support victims of verbal bullying, fostering safer and more inclusive educational environments. Keywords: cognitive behavioral therapy, group counseling, self-esteem, verbal bullying, adolescents